Pengaruh Penggunaan Set Up Voltage dengan Varian Bahan Bakar terhadap Torsi dan Daya Pada Motor Honda Beat - Yusrian, Misbah Alfi; Wijayanto, Danar Susilo; Rohman, Ngatou (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
The purposes of this study are: (1) To determine the effect of using Step Up Voltage on torque and power of Honda Beat 2013 motorcycles. (2) To determine the effect of using Pertalie and Pertamax fuel variations on torque and power of Honda Beat 2013 motorcycles. (3) Knowing the best configuration of Step Up Voltage and fuel variations on the torque of the 2013 Honda Beat motorcycle. The research method used is experimental. The data of this research was obtained by measuring the sample of Honda Beat 2013 motorcycle. The independent variable was the use of Step Up Voltage with a voltage variation of 13.7 V to 14.7 V with a range of 0.2 V with Pertamax and Pertalite fuel. The dependent variable is the maximum torque of the axle and the maximum power of the axle which is measured using a dynamometer. The data obtained were then analyzed using a comparative descriptive technique by describing the data in the form of graphs, statistics and tables. From these data, a comparison is made between groups of data. The results of this study are: (1) The use of Step Up Voltage can increase the torque and power of the Honda Beat 2013 motorcycle. The largest increase in torque is at a voltage setting of 13.9 V with an average increase of 0.44 N.m from standard conditions. The average maximum power increase of the largest axle is at a voltage setting of 14.1 V, which is 0.30 HP from standard conditions. (2) The use of Pertamax fuel can increase the torque and power of the Honda Beat 2013 motorcycle. The average torque produced is 19.98 Nm, an increase of 0.26 Nm from pertalite fuel and produces an average power of 7.47 HP, an increase of 0.34. HP of pertalite fuel. (3) The best configuration is obtained from the use of a 13.9 V Step Up Voltage combined with Pertamax fuel. Torque increased by 0.44 N.m from standard conditions to 20.41 N.m and power increased by 0.20 HP from standard conditions to 7.67 HP